Towards optimisation of compound rotorcraft - Zhang, T.; Barakos, G.N. (My University, 2019)
This work presents a tool-chain development for aerodynamic analysis and optimisation of compound rotorcraft. An automation framework for geometry composition and grid generation using ICEM Hexa is proposed, and variable applications are presented. High-fidelity CFD simulations of ducted fans are first performed to validate the in-house solver HMB3. Detailed analyses of the ducted fan and comparisons against experiments and simpler methods are presented, and good correlation can be noted. A compound helicopter model is then assembled, consisting of a parametrised Dauphin-like fuselage, ducted fans for auxiliary thrust, and a main rotor. Simulation methods of several fidelity levels using steady/unsteady actuator disks and resolved blades are conducted and evaluated. Analyses of the aerodynamics and flow features are then presented.